2016
DOI: 10.1016/s1470-2045(15)00515-x
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus versus sunitinib for patients with metastatic non-clear cell renal cell carcinoma (ASPEN): a multicentre, open-label, randomised phase 2 trial

Abstract: Novartis and Pfizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
267
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(300 citation statements)
references
References 27 publications
(36 reference statements)
9
267
0
7
Order By: Relevance
“…ChRCC is relatively indolent despite its usual presentation as larger tumors (10), yet ~5%-10% of patients eventually develop metastases (11,12). Thus far, there are no genomic biomarkers that predict metastatic progression, and no standard of care for metastatic chRCC (M-chRCC) (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…ChRCC is relatively indolent despite its usual presentation as larger tumors (10), yet ~5%-10% of patients eventually develop metastases (11,12). Thus far, there are no genomic biomarkers that predict metastatic progression, and no standard of care for metastatic chRCC (M-chRCC) (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…68 The ASPEN trial demonstrated sunitinib was superior to everolimus for PFS. 69 Thus, sunitinib is the preferred first-line treatment for nonclear-cell RCC.…”
Section: Non-clear-cell Histologymentioning
confidence: 99%
“…The RAPTOR trial evaluated everolimus as monotherapy in pRCC and found that it was beneficial, with a median OS of 21 months and a similar difference between type 1 (median OS 28 mo) and type 2 (median OS 20 mo) (19). ASPEN (20) and ESPN (21) are two recently published phase 2 trials comparing sunitinib and everolimus as first line therapy in patients with metastatic non-clear cell RCC. Of note, there were significant differences in the trial populationsthe ESPN trial included sarcomatoid clear cell RCC and 39.7% pRCC whereas ASPEN did not allow any clear cell RCC and 66% of subjects had pRCC.…”
Section: Therapies For Papillary Renal Cell Carcinomamentioning
confidence: 99%